Analysis Of Recognition And Work Environment On Teacher Performance With Job Satisfaction As Mediating Variable In Smp Negeri 1 Binjai - Hamnah Yasari; Elfitra Desy Surya; Kiki Farida Ferine (Jurnal Fokus Manajemen, 2026)
Teacher performance is a key factor in improving the quality of education in schools. Optimal teacher performance is influenced by various organizational factors, including rewards and work environment, as well as job satisfaction, which is an important psychological factor. This study aims to analyze the effect of rewards and work environment on teacher performance with job satisfaction as a mediating variable at SMP Negeri 1 Binjai. This study uses a quantitative approach with a survey method. The population in this study was all 64 teachers at SMP Negeri 1 Binjai, who were also used as the research sample. Primary data were collected through questionnaires and analyzed using Partial Least Squares (PLS) with the help of the SmartPLS application. The results showed that rewards and work environment had a positive and significant effect on teacher performance and job satisfaction. Furthermore, job satisfaction was proven to have a positive and significant effect on teacher performance. The results of the indirect effect test showed that job satisfaction acted as a mediating variable in the relationship between rewards and teacher performance, as well as between the work environment and teacher performance. The coefficient of determination value showed that rewards and the work environment were able to explain 50% of the variation in job satisfaction, while rewards, the work environment, and job satisfaction were able to explain 61.8% of the variation in teacher performance. These findings indicate that improvements in teacher performance can be achieved through an effective reward system, improvements in a conducive work environment, and strengthening teacher job satisfaction. This study is expected to serve as a basis for schools in formulating managerial policies to improve teacher performance and the quality of education